Pengaruh Sistem Informasi Akuntansi Terhadap Efektivitas Penjualan Dengan Pengendalian Intern Sebagai Variabel Intervening : Studi Empiris Pada PT. Nusantara Surya Sakti di Kabupaten Ende dan Nagekeo - Abdurachman, Irnawati; Djou, Laurentius D Gadi; Sayang, Sabulon (Program Studi Akuntansi Universitas Flores, 2021)
This study aims to determine the effect of each variable, namely the accounting information system on sales effectiveness, with internal control as an intervening variable at PT. Nusantara Surya Sakti in Ende and Nagekeo Regencies. The population in this study was 86 employees. Samples taken as many as 46 respondents. The method used is a quantitative research method. This research uses primary data that is questionnaire. Data were analyzed using multiple regression analysis and path analysis which are managed through SPSS Statistics 25 software. The results showed that the accounting information system affects the effectiveness of sales with a significance value of 0,032 less than 0,05. However, the Path Analysis test results show that the value of direct influence has a smaller value compared to the indirect effect (0,193<l,030), so it is concluded that there is a mediating influence between the accounting information system on sales effectiveness through internal control.